2017
DOI: 10.1155/2017/4271671
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Perioperative Topical Ketorolac 0.5% on Macular Thickness after Uneventful Phacoemulsification

Abstract: Background To evaluate the effects of topical 0.5% ketorolac treatment combined with topical steroids on macular thickness in cases who had uneventful phacoemulsification surgery. Methods 58 eyes of 58 consecutive cases were included. The mean foveal thickness (MFT), parafoveal thickness (ParaFT), and perifoveal thickness (PeriFT) measurements were performed with optical coherence tomography (RTVue-100, Optovue, Fremont, CA, USA) preoperatively and at postoperative 1 week, 1 month, and 2 months. All cases rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The peak of hypertension observed 24 hours after surgery was described as a common postoperative effect in rabbits. Such an occurrence was associated with BAB disruption, excessive motion of fluids during irrigation, manipulation of intraocular structures and even permanence of viscoelastic agents in the AC (7,8,20,21) . The IOP reductions observed at TP 15 compared with TP 0 in both groups were likely a reflection of postoperative uveitis.…”
Section: Discussionmentioning
confidence: 99%
“…The peak of hypertension observed 24 hours after surgery was described as a common postoperative effect in rabbits. Such an occurrence was associated with BAB disruption, excessive motion of fluids during irrigation, manipulation of intraocular structures and even permanence of viscoelastic agents in the AC (7,8,20,21) . The IOP reductions observed at TP 15 compared with TP 0 in both groups were likely a reflection of postoperative uveitis.…”
Section: Discussionmentioning
confidence: 99%
“…So, we started topical NSAID treatment at postoperative month 1, in addition to topical steroid which was given for post-cataract treatment. Even still, there are no evidence-based guidelines for the treatment of Irvine-Gass syndrome, several studies have reported signi icant reductions in the macular edema with the topical therapy, after cataract surgery [11][12][13][14]. Combination therapy with topical NSAID and corticosteroidis signi icantly more effective than only corticosteroid in treatment of Irvine-Gass syndrome [15].…”
Section: Discussionmentioning
confidence: 99%
“…Dal et al evaluated the effects of topical 0.5% ketorolac treatment, which started 2 days prior to the surgery combined with topical steroids on macular thickness in cases who had no risk factors and uneventful phacoemulsification. Control group was patients who received only steroids and results showed that the increase in mean foveal thickness at the first week, first and second months after surgery was significantly lower in NSAIDs group but again, authors excluded all PCME cases from the statistical analysis [82].…”
Section: Inflammation Control and Pseudophakic Cystoid Macular Oedema...mentioning
confidence: 99%